Effectiveness Of Culture-Sensitive Education Using the Transtheoretical Model On Under-Five Family Feeding Practices - Sambo, Mery; Fransiska Anita Ekawati Rahayu Sa’pang (Universitas Islam Negeri Alauddin Makassar, 2025)
Stunting remains a chronic nutritional problem in Indonesia, with a prevalence of 21.6% in 2023 and 27.4% in South Sulawesi. Feeding practices are an important factor in preventing stunting, but existing interventions are often general in nature and do not take into account cultural aspects and families' readiness to change their behavior. This study used a quasi-experimental one-group pre-test post-test design on 55 mothers of children under five years in the working area of the Simbang Community Health Center, Maros District. The intervention was cultural-sensitive nutrition education based on the Transtheoretical Model (TTM). Data were collected using the Feeding Practice Questionnaire and analyzed using the Wilcoxon Signed Rank test. The results showed a significant increase in the stage of behavioral change, with Z = −4.523, p < 0.001, and effect size r = 0.61. The TTM-based intervention was effective in improving family feeding practices. This approach helped families progress gradually to the maintenance stage and proved to be more effective than conventional nutrition education.